The MeteoMet project – metrology for meteorology: challenges and results. (1st December 2015) - Merlone, A.; Lopardo, G.; Sanna, F.; Bell, S.; Benyon, R.; Bergerud, R. A.; Bertiglia, F.; Bojkovski, J.; Böse, N.; Brunet, M.; Cappella, A.; Coppa, G.; et al.
ABSTRACT: The study describes significant outcomes of the 'Metrology for Meteorology' project, MeteoMet, which is an attempt to bridge the meteorological and metrological communities. The concept of traceability, an idea used in both fields but with a subtle difference in meaning, is at the heart of the project. For meteorology, a traceable measurement is the one that can be traced back to a particular instrument, time and location. From a metrological perspective, traceability further implies that the measurement can be traced back to a primary realization of the quantity being measured in terms of the base units of the International System of Units, the SI. These two perspectives reflect long‐standing differences in culture and practice and this project – and this study – represents only the first step towards better communication between the two communities. The 3 year MeteoMet project was funded by the European Metrology Research Program (EMRP) and involved 18 European National Metrological Institutes, 3 universities and 35 collaborating stakeholders including national meteorology organizations, research institutes, universities, associations and instrument companies. The project brought a metrological perspective to several long‐standing measurement problems in meteorology and climatology, varying from conventional ground‐based measurements to those made in the upper atmosphere. It included development and testing of novel instrumentation as well as improved calibration procedures and facilities, instrument intercomparison under realistic conditions and best practice dissemination. Additionally, the validation of historical temperature data series with respect to measurement uncertainties and a methodology for recalculation of the values were included.